Bio-inspired and optimized interlocking features for strengthening metal/polymer interfaces in additively manufactured prostheses. (15th October 2018) - Alsheghri, Ammar A.; Alageel, Omar; Amine Mezour, Mohamed; Sun, Binhan; Yue, Stephen; Tamimi, Faleh; Song, Jun
Graphical abstract: Abstract: Biomedical and dental prostheses combining polymers with metals often suffer failure at the interface. The weak chemical bond between these two dissimilar materials can cause debonding and mechanical failure. This manuscript introduces a new mechanical interlocking technique to strengthen metal/polymer interfaces through optimized additively manufactured features on the metal surface. To reach an optimized design of interlocking features, we started with the bio-mimetic stress-induced material transformation (SMT) optimization method. The considered polymer and metal materials were cold-cured Poly(methyl methacrylate) (PMMA) and laser-sintered Cobalt-Chromium (Co-Cr), respectively. Optimal dimensions of the bio-inspired interlocking features were then determined by mesh adaptive direct search (MADS) algorithm combined with finite element analysis (FEA) and tensile experiments such that they provide the maximum interfacial tensile strength and stiffness while minimizing the stress in PMMA and the displacement of PMMA at the Co-Cr/PMMA interface. The SMT optimization process suggested a Y-shape as a more favorable design, which was similar to mangrove tree roots. Experiments confirmed that our optimized interlocking features increased the strength of the Co-Cr/PMMA interface from 2.3 MPa (flat interface) to 34.4 ± 1 MPa, which constitutes 85% of the tensile failure strength of PMMA (40.2 ± 1 MPa). Statement of Significance: The objective of this study was to improve metal/polymer interfacial strength in dental and orthopedic prostheses. This was achieved by additive manufacturing of optimized interlocking features on metallic surfaces using laser-sintering. The interlocking design of the features, which was a Y-shape similar to the roots of mangrove trees, was inspired by a bio-memetic optimization algorithm. This interlocking design lowered the PMMA displacement at the Co-Cr/PMMA interface by 70%, enhanced the interfacial strength by more than 12%, and increased the stiffness by 18% compared with a conventional bead design, meanwhile no significant difference was found in the toughness of both designs.